The associations of competitive trait anxiety and personal control with burnout in sport - Aoyagi, M. W.; Burke, K. L.; Joyner, A. B.; Hardy, C. J.; Hamstra, M. S. (Athletic Insight - The Online Journal of Sport Psychology, 2009)
The incidence of athlete burnout among competitive athletes from youth, high school, and collegiate age groups as well as the associations between competitive trait anxiety and personal control with athlete burnout were explored. The sample consisted of 153 competitive athletes (58 men, 95 women) from three age groups. The Eades Athlete Burnout Inventory (Eades, 1990), Sport Anxiety Scale (Smith, Smoll, & Schutz, 1990), and a modified version of the Control Over One`s Sport Environment scale (Tetrick & Larocco, 1987) were completed by 30 youth (ages 10-13 years), 67 high school (ages 14-18 years), and 56 college (ages 18-22 years) athletes. Also, a directional scale was added to the Sport Anxiety Scale on which athletes rated the extent to which items were perceived as helpful or hurtful to performance. Results revealed that overall the sample reported a low incidence of burnout (M = 62.88, SD = 33.67). A moderate to strong positive relationship (r = .645) between athlete burnout and competitive trait anxiety was found as well as a moderate negative correlation (r = -.433) between athlete burnout and perceived control. Youth athletes (M = 28.21, SD = 18.41) scored significantly (p < .05) lower on the EABI than high school (M = 69.66, SD = 21.93) and college (M = 72.95, SD = 39.24) athletes, and women (M = 68.89, SD = 37.49) reported significantly (p < .05) higher burnout scores than men (M = 52.19, SD = 22.19). Somatic anxiety was perceived to be helpful to performance (M = 2.50, SD = 12.95) while worry (M = -1.75, SD = 11.34) and concentration disruption (M = -1.01, SD = 8.54) were perceived as detrimental to performance. Implications of results and directions for future research are discussed.